Hubungan Riwayat Berat Badan Lahir Dengan Kejadian Stunting Pada Balita Usia 24-60 Bulan Di Puskesmas Jogonalan - Lilik Hartati; anna uswatun (Stikes Muhammadiyah Klaten, 2020)
Stunting was defined as height for age below -2 the standard median child growth curve. Stunting factors such as birth weight, stimulation and improper care of children, lack of nutritional intake, and recurrent infections and various other environmental factors. Birth weight is the baby's weight measured within the first 1 hour after birth. The purpose of this study was to determine the relationship between birth weight and the incidence of stunting in children aged 24-60 months at Jogonalan Health Center. This research is a descriptive correlation study with the method used is retrospective. The population in this study were 190 stunting infants aged 24-60 months at Jogonalan Health Center. The sampling technique used the Simple Random Sampling Technique in a random way with a sample size of 48 infants. The instrument in this study used an observation sheet. Data analysis used Kendall Tau correlation calculation. The results of the study most of the respondents had a history of normal birth weight as many as 36 toddlers (75%) with a short category 23 toddlers (69.7%) and a very short category 13 toddlers (86.7%). The conclusion of the study based on the results of Kendall Tau correlation calculations concluded that there was no relationship between a history of birth weight and the incidence of stunting in toddlers aged 24-60 months at Jogonalan Health Center where p = 0.680 (p> 0.05). Suggestions for parents to increase knowledge about growth problems in children, one of which is stunting